Experimental study on the effectiveness of Electrochemical Chloride Extraction (ECE) for reinforced concrete - De Brabandere Justine; Wybo Manon; Van Belleghem Bjorn; Godefroidt Emile; Soetens Tim (MATEC Web of Conferences)
Chloride-induced corrosion is a widespread damage phenomenon in reinforced concrete structures that leads to a substantial reduction in their service life. Fortunately, different repair techniques are available, including electrochemical techniques, such as cathodic protection (CP) and electrochemical chloride extraction (ECE). While CP has proven to be an effective method to stop reinforcement corrosion, ECE, where an electrical field is used to force chloride ions out of concrete, is less seen in practice. In this research, the influence of different parameters on the effectiveness of ECE is investigated. The results of this research show that for concrete samples containing around 0.75 m% Cl- ~cement mixed-in chlorides the removal rate ranged from 50-60% in the concrete cover to 20-30% around the reinforcement and behind it, irrespective of different influencing factors. However, when a higher initial chloride concentration, namely 2.68 m% Cl- ~cement was present within the concrete, the removal rate was 1.4 times higher. Besides, when an ingressed chloride profile was created with approximately 0.75 m% Cl- ~cement at the level of reinforcement, the removal rate was between 1.7 and 2.8 times higher. Lastly, it must be noted that an examination of the corrosion potential indicated that all samples had a low probability of reinforcement corrosion after ECE-treatment, showing that ECE successfully removed enough chlorides to reduce the risk for active corrosion.